2011
DOI: 10.1007/s00417-011-1699-4
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte/macrophages promote vasculogenesis in choroidal neovascularization in mice by stimulating SDF-1 expression in RPE cells

Abstract: Background Monocyte-macrophages play important roles in choroidal neovascularization (CNV); however, the mechanism is unclear. This study investigated the effects of monocyte depletion on laser-induced CNV in mice, especially the involvement of bone marrow-derived cells (BMCs) and underlying molecular mechanisms. Methods Clodronate-liposomes (lip) were used to deplete monocytes and their effect on retinal pigmental epithelium (RPE) cells, endothelial cells, and BMCs was analyzed. Green fluorescent protein (GFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In addition to the angiogenic factors associated with CNV, the extracellular matrix and surrounding cells facilitate survival and stabilize endothelial cells [26]. Animal studies showed that inflammatory cells such as macrophages play a critical role in choroidal angiogenesis through the recruitment and activation in CNV lesions to release pro-angiogenic factors [27,28]. Thus, considering the various pathogenic factors involved in CNV, therapies targeting multiple participants in CNV pathogenesis would provide benefits beyond a single-target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the angiogenic factors associated with CNV, the extracellular matrix and surrounding cells facilitate survival and stabilize endothelial cells [26]. Animal studies showed that inflammatory cells such as macrophages play a critical role in choroidal angiogenesis through the recruitment and activation in CNV lesions to release pro-angiogenic factors [27,28]. Thus, considering the various pathogenic factors involved in CNV, therapies targeting multiple participants in CNV pathogenesis would provide benefits beyond a single-target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…While perturbation of CCR2 signaling was shown to lead to accumulation of debris or inflammatory cells in the retina, 20,57,58 macrophage depletion can either enhance or suppress the development of CNV. 13,59,60 This contradicting role of macrophages may be explained by the polarization of macrophages into specialized subsets having diverse effects. 18,19,61,62 In contrast to the other inflammatory disorders in which the CD14þCD16þ subset of activated circulating monocytes, a precursor of tissue macrophages, plays a role, 63 limited data exist with respect to the involvement of monocytes in AMD.…”
Section: Discussionmentioning
confidence: 99%
“…From total RNA samples, reverse transcription was performed using SuperScript III Transcriptions kit (Invitrogen, Carlsbad, CA) and oligo(dT)primers. With SDF-1 primers, SDF-1 cDNA was analyzed (5=-GAT TGT AGC CCG GCT GAA GA -3= and 5=-TTC GGG TCA ATG CAC ACT TGT -3=) on an iCycler iQ Real-Time Detection System (Bio-Rad, Hercules, CA) (40). As control for the amount of starting template, murine 18S mRNA (primers: 5=-CCA TCC AAT CGG TAG TAG CG-3= and 5=-GTA ACC CGT TGA ACC CCA TT -3=) was amplified in identical reactions.…”
Section: Methodsmentioning
confidence: 99%